CYTOGENETIC AND SYSTEMIC TOXICITY INDUCED BY SILVER AND COPPER(II) OXIDE NANOPARTICLES AND THEIR MIXTURE IN THE SOMATIC CELLS OF THREE EUKARYOTIC ORGANISMS (2019)
Silver (Ag) and copper(II) oxide (CuO) nanoparticles are used in personal care products because of their antimicrobial properties. Their continual release into the environment may enhance genotoxic effects in the ecosystem, a condition widely reported from in vitro studies. However, in vivo, there is insufficient information on DNA and systemic damage, as well as the effect of the mixture of these nanoparticles in aquatic and terrestrial biota. This study was designed to investigate the genetic and systemic toxicity of Ag and CuO nanoparticles, singly and combined in somatic cells of three eukaryotic organisms and their mechanism of DNA damage. The selected eukaryotic organisms were onion (Allium cepa Linnaeus), mud catfish (Clarias gariepinus Burchell) and mice (Mus musculus Linnaeus). Cytogenotoxicity of Ag, CuO and their mixture (1:1) was investigated at different concentrations using the A. cepa chromosome aberration assay (0, 5-80 mg/L; n=64), micronucleus assessment in peripheral blood of juvenile catfish (0, 6.25-100 mg/L; n=80) and bone marrow of male mice (0, 18.75-300 mg/kg; n=64). Haematological parameters [haemoglobin concentration, Packed Cell Volume (PCV), Red Blood Cell (RBC) and White Blood Cell (WBC) counts] were assessed in catfish and mice. The histopathology of their liver and fish gill was done using standard protocols. Mechanism of DNA damage was investigated by analysing hepatic oxidative stress biomarkers [Superoxide Dismutase (SOD), reduced Glutathione and Malondialdehyde] in both catfish and mice. Interaction Factor (IF) of the mixture was calculated according to standard method. Data were analysed using descriptive statistics and ANOVA at α0.05. In A. cepa, there was a concentration-dependent increase in the percentage frequency of dividing cells with Ag (1.3-1.6 fold); and decrease with CuO (1.1-16.8 fold) as well as mixture (1.5-2.7 fold). The frequency of aberrant chromosomes significantly increased only with Ag (3.3-8.7 fold) and mixture (1.5-4.6 fold) compared with control. Micronuclei induction with Ag, CuO and their mixture significantly increased in catfish (1.1-1.9, 1.4-2.2 and 1.6-2.9 fold), and mice (1.0-2.9, 1.1-4.8 and 1.5-3.1 fold), respectively. Haemoglobin concentration, PCV, RBC and WBC significantly decreased only in both nanoparticles and their mixture for catfish. Gill lamella hyperplasia and hepatocellular necrosis were observed in catfish and mice respectively. In catfish, there were significant alterations in SOD activities (1.1-2.2 fold increase with Ag and CuO; and 1.6-2.0 fold decrease with mixture). Alongside, reduced Glutathione and Malondialdehyde levels (1.1-1.8; and 1.1-2.4 fold increase with Ag and CuO, respectively; and 1.1-2.8 fold decrease with mixture) were altered. In mice, there were significant alterations in SOD activities (1.1-1.6 fold decrease with Ag and CuO; and 1.3-1.6 fold increase with mixture), Malondialdehyde (1.1-1.5 fold increase with Ag and mixture; and 1.1-2.0 fold decrease with CuO) and reduced Glutathione levels (1.1-1.2 fold increase with Ag and decrease with CuO). The IF showed that interaction between Ag and CuO was antagonistic for cytogenotoxicity and oxidative stress. Silver, copper(II) oxide and their mixture induced genomic disruption in the three organisms with systemic anomalies in Clarias gariepinus and Mus musculus. Oxidative stress in the exposed cells was responsible for the observed DNA damage.